(Im)politeness in the discourse on crime: naming of offender - Jakimovienė, Sigita (Lietuvių kalba, 2017)
By focusing on the study of naming of an offender in the media in one particular case when father killed his two children in Saviečiai, this paper provides a perspective on the discourse on crime as the discourse governed by the strategies of impoliteness. The face management theory (Brown and Levinson 1978, 1987) and the insight of face attacking acts (Austin 1987) is considered here to be generally useful for the analyses of the discourse on crime which is, as a rule, about negatively evaluated persons and their actions. Having analysed 46 crime reports in the Lithuanian media published in the period of one month on January 2016, 36 different nominal references of the offender have been found. The results reveal that the level of politeness in the discourse on crime can be assessed considering the naming of an offender. In this discourse the naming of the offender is performed mainly as face attacking acts: 1) a naming word has a negative emotional evaluation or is an obvious insult or nickname which might be considered as a dysphemism (vaikžudys, smurtautojas, skriaudikas, žudikas, siaubūnas, antžmogis, monstras, budelis, išgama, degradas, navikas, alkoholikas, girtuoklis, chuliganas); 2) neutral naming words (vyras, tėvas, A. Beras, etc.) are modified by means of extended attributes that indicate the crime and the victims, the location of the crime. In fact, it often expresses a straightforward negative assessment. This type of naming of the offender with an additional indication of the time of the offense, the date of birth of the offender, the age and sex of the victims, is voluminous (up to 25 words) in this discourse. Such a naming becomes like a brief statement or a story in itself. Developing a discourse on this crime, this type of naming is continuously employed as if there were fears that readers won’t identify the offender. Such a naming or even a nickname substitutes the proper name of the offender in the titles of the articles. The term suspect, which might soften the assertiveness of a statement, is rarely used. The results disclose that to speak negatively in the media articles about crime (to use nicknames, insults, to emphasize the negativity and criticism, to lie in order to make an impression of the negativity) is the norm, so the discourse on crime can be seen as a discourse, allowing the strategies of impoliteness.
Keywords: discourse on crime; linguistic politeness; linguistic impoliteness; face attacking acts; naming; dysphemisms